Integrated coastal management in Brazil: analysis of the National Coastal Management Plan and selected tools based on international standards - Klumb-Oliveira,Leonardo Azevedo (2015)
The Integrated Coastal Zone Management (ICZM) in Brazil is a political-institutional process, manifested in the establishment of the National Coastal Management Plan (NCMP) and in the formulation and implementation of specific tools for territorial planning in the coastal zone, as well as other activities related to ICZM in Brazil. This work analyses some official documents related to the Brazilian NCMP and to the frequently used tools for performing ICZM in Brazil: Macrodiagnostic of Coastal Zone, Orla Project and Coastal Ecological and Economic Zoning. The analysis is based on legislative, ecological and socioeconomic indicators, found in the Handbook for Measuring the Progress and Outcomes of Integrated Coastal and Ocean Management, published in 2006 by the Intergovernmental Oceanographic Commission. The results indicate adequacy of NCMP and tools on the definition and delimitation of the coastal zone, as the institutional processes of coordination and cooperation within the ICZM and about the diagnostics and the territorial planning of the coastal zone. However, the Brazilian NCMP as the cited tools still need to fully meet the major global goal of the ICZM, as internationally defined by the Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection (GESAMP), with respect to the improvement of the life quality of coastal populations who depends on the sea resources and with respect to the environmental conservation of the Brazilian coastal zone. With the wide dissemination of results, is expected to contribute to the improvement of NCMPs and ICZM tools maintained worldwide, since we emphasize the importance of including the international general objectives of the ICZM, as well as inclusion the dimensions of sustainability in the ICZM processes, so try to ensure economic growth, coupled with respect to coastal populations and environmental conservation in coastal areas.